Alternância de hospedeiros de criação e efeito de bioinseticidas no parasitismo de Trichogramma pretiosum em ovos de Plutella xylostella - Figueroa, Claudio Antonio Salas [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Species of the Trichogramma Westwood (Hymenoptera: Trichogrammatidae) genus are used to control Lepidoptera pests in many crops of economic importance, however, little is known about their parental or breeding hosts; this may be a limiting factor in the search and localization of the target pest in field conditions. In this perspective, the purpose of the present study was to breed the parasitoid Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) alternating the breeding hosts Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) and target, Plutella xylostella Linnaeus (Lepidoptera: Plutellidae), so as to assess the influence of hosts alternation in the acceptance and preference. To this end T. pretiosum was bred for successive generations in the alternate host C. cephalonica and later on in the natural host, P. xylostella. The number of parasited eggs and the emergence percentage per host was assessed in each generation. The preference towards both hosts was also determined in each generation, using experimental sands, with and without choice possibilities. In this way it was possible to determine the number of generations required for the parasitoid to increase its acceptance of the natural host P. xylostella, an unpredictable factor for the success of biological control of this important pest; thus setting the basis to carry out improvements in the mass breeding systems of these parasitoids. The effect of products based on Bacillus thuringiensis Berliner on the parasitic performance of T. pretiosum upon P. xylostella eggs was also studied. The evaluated T. pretiosum Tp8 strain was recorded in the preference tests with host's alternation and in the free choice tests, showing a preference towards the C. cephalonica host. However, when P. xylostella was offered singly with no choice possibilities, the parasitism and emergence levels obtained were,66% and 64% respectively, thus showing that the conditioning towards ...

Espécies de Trichogramma Westwood (Hymenoptera: Trichogrammatidae) são utilizadas para o controle de lepidópteros-praga em várias culturas de importância econômica. Contudo, pouco se conhece sobre seus hospedeiros preferenciais, o que pode ser fator limitante para a busca e localização da praga-alvo em condições de campo. Este estudo teve por objetivos a criação de Trichogramma pretiosum Riley linhagem TP8 no hospedeiro alternativoCorcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) e no hospedeiro alvoPlutella xylostella Linnaeus (Lepidoptera: Plutellidae),para avaliar a influência da alternância de hospedeiros na aceitação e preferência pelo parasitoide. T. pretiosumlinhagem Tp8 foi criado em C. cephalonica por gerações sucessivas e, posteriormente emP. xylostella. Em cada geração foi avaliado o número de ovos parasitados e a porcentagem de emergência em cada hospedeiro; a preferência para ambos os hospedeiros, utilizando-se arenas experimentais com e sem chance de escolha e, o número de gerações necessárias para o parasitoide aumentar sua aceitação pelo hospedeiro natural P. xylostella. Também foi objetivo estabelecer bases para a melhoria dos sistemas de criação massal de T. pretiosum e avaliar o efeito de produtos formulados com Bacillus thuringiensis Berliner no desempenho do parasitismo de T. pretiosum em ovos de P. xylostella. Verificou-se que a linhagem Tp8 de T. pretiosum, tanto nos testes de preferência com alternância de hospedeiros quanto nos de livre escolha, tevepreferência por C. cephalonica. Quando foram oferecidos ovos deP. xylostella sem chance de escolha, os níveis de parasitismo e emergência obtidos foram de 66% e 64%, respectivamente, demostrando que o condicionamento sobre o hospedeiro parental pode ser alterado em favor da aceitação e parasitismo da espécie-alvo a controlar. Fêmeas de T. pretiosum criadas por uma geração sobre P. xylostella aumentaram sua afinidade por...
Keywords: Ovos; Relação hospedeiro-parasito; Parasitóides; Pragas agricolas - Controle biologico; Inseticidas biológicos; Agricultural pests Biological control